2014
DOI: 10.3791/51482
|View full text |Cite
|
Sign up to set email alerts
|

An Engulfment Assay: A Protocol to Assess Interactions Between CNS Phagocytes and Neurons

Abstract: Phagocytosis is a process in which a cell engulfs material (entire cell, parts of a cell, debris, etc.) in its surrounding extracellular environment and subsequently digests this material, commonly through lysosomal degradation. Microglia are the resident immune cells of the central nervous system (CNS) whose phagocytic function has been described in a broad range of conditions from neurodegenerative disease (e.g., beta-amyloid clearance in Alzheimer's disease) to development of the healthy brain (e.g., synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 29 publications
4
91
0
Order By: Relevance
“…To quantify the volume of engulfed Ab, fluorescence outside of astrocytes or microglia was subtracted from the image, and the remaining engulfed fluorescence was surface-rendered and calculated (Schafer et al, 2012(Schafer et al, , 2014. 3D volume surface renderings of each z-stack were created using Imaris 8.4.1 (Bitplane), and the volume of glial cells and Ab compartments (IC16 and methoxy-XO4) was determined from surface-rendered images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the volume of engulfed Ab, fluorescence outside of astrocytes or microglia was subtracted from the image, and the remaining engulfed fluorescence was surface-rendered and calculated (Schafer et al, 2012(Schafer et al, , 2014. 3D volume surface renderings of each z-stack were created using Imaris 8.4.1 (Bitplane), and the volume of glial cells and Ab compartments (IC16 and methoxy-XO4) was determined from surface-rendered images.…”
Section: Discussionmentioning
confidence: 99%
“…3D volume surface renderings of each z-stack were created using Imaris 8.4.1 (Bitplane), and the volume of glial cells and Ab compartments (IC16 and methoxy-XO4) was determined from surface-rendered images. To quantify the volume of engulfed Ab, fluorescence outside of astrocytes or microglia was subtracted from the image, and the remaining engulfed fluorescence was surface-rendered and calculated (Schafer et al, 2012(Schafer et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…1g-o and Supplementary Fig. 3a) 1,31 . These inputs were largely localized within the microglia, but not yet significantly associated with lysosomes ( Fig.…”
Section: Whisker Lesioning Induces Microglial Engulfment Of Tc Inputsmentioning
confidence: 99%
“…Using this system, the investigators observed microglial processes closely apposed to presynaptic inputs undergoing remodeling within the dLGN, data consistent with previous live imaging and EM data (Tremblay et al 2010). Subsequently, a novel in vivo assay was developed in mice to determine if microglia were engulfing inputs (Schafer et al 2012(Schafer et al , 2014. In this engulfment assay, presynaptic inputs within the dLGN are fluorescently labeled by intraocular injection of anterograde dyes that are highly stable and resistant to lysosomal degradation (i.e., cholera toxin b subunit conjugated to Alexa dyes).…”
Section: Dp Schafer and B Stevensmentioning
confidence: 99%